Tau Isoforms Imbalance Impairs the Axonal Transport of the Amyloid Precursor Protein in Human Neurons - Lacovich, Valentina; Espindola, Sonia L; Alloatti, Matías; Pozo Devoto, Victorio; Cromberg, Lucas E; Čarná, Mária E; Forte, Giancarlo; Gallo, Jean-Marc; Bruno, Luciana; Stokin, Gorazd B; Avale, M Elena; Falzone, Tomás L (The Journal of neuroscience, 2017)
UNLABELLED: Tau, as a microtubule (MT)-associated protein, participates in key neuronal functions such as the regulation of MT dynamics, axonal transport, and neurite outgrowth. Alternative splicing of exon 10 in the tau primary transcript gives rise to protein isoforms with three (3R) or four (4R) MT binding repeats. Although tau isoforms are balanced in the normal adult human brain, imbalances in 3R:4R ratio have been tightly associated with the pathogenesis of several neurodegenerative disorders, yet the underlying molecular mechanisms remain elusive. Several studies exploiting tau overexpression and/or mutations suggested that perturbations in tau metabolism impair axonal transport. Nevertheless, no physiological model has yet demonstrated the consequences of altering the endogenous relative content of tau isoforms over axonal transport regulation. Here, we addressed this issue using a trans-splicing strategy that allows modulating tau exon 10 inclusion/exclusion in differentiated human-derived neurons. Upon changes in 3R:4R tau relative content, neurons showed no morphological changes, but live imaging studies revealed that the dynamics of the amyloid precursor protein (APP) were significantly impaired. Single trajectory analyses of the moving vesicles showed that predominance of 3R tau favored the anterograde movement of APP vesicles, increasing anterograde run lengths and reducing retrograde runs and segmental velocities. Conversely, the imbalance toward the 4R isoform promoted a retrograde bias by a significant reduction of anterograde velocities. These findings suggest that changes in 3R:4R tau ratio has an impact on the regulation of axonal transport and specifically in APP dynamics, which might link tau isoform imbalances with APP abnormal metabolism in neurodegenerative processes. SIGNIFICANCE STATEMENT: The tau protein has a relevant role in the transport of cargos throughout neurons. Dysfunction in tau metabolism underlies several neurological disorders leading to dementia. In the adult human brain, two tau isoforms are found in equal amounts, whereas changes in such equilibrium have been associated with neurodegenerative diseases. We investigated the role of tau in human neurons in culture and found that perturbations in the endogenous balance of tau isoforms were sufficient to impair the transport of the Alzheimer's disease-related amyloid precursor protein (APP), although neuronal morphology was normal. Our results provide evidence of a direct relationship between tau isoform imbalance and defects in axonal transport, which induce an abnormal APP metabolism with important implications in neurodegeneration.
Keywords: Alzheimer's; myši; Animals; kultivované buňky; tau; Cells, Cultured; splicing; axonal transport; neurony; APP; Amyloid beta-Protein Precursor; Protein Isoforms; Humans; protein - isoformy; Tauopathies; Neurons; lidé; Mice; zvířata; axonální transport; tauopatie; tauopathies; Axonal Transport; amyloidový prekurzorový protein beta; tau Proteins; proteiny tau